2019
DOI: 10.1186/s12881-019-0894-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oxytocin receptor single nucleotide sequence variants on contractility of human myometrium: an in vitro functional study

Abstract: BackgroundOxytocin receptor (OXTR) gene variants have been shown to affect the prevalence of preterm birth, mode of delivery and oxytocin (OXT) requirements for labor induction and augmentation. We hypothesized that this might be associated with different myometrium responses to oxytocin. Our aim was to investigate the influence of a selection of eight OXTR gene single nucleotide variants on oxytocin-induced stimulation of human myometrium contractility in vitro.MethodsHuman myometrium biopsies were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…It has a strong contractile effect on the uterus at all stages of pregnancy. CTI can induce rhythmic uterine contraction by binding to oxytocin receptors on uterine smooth muscle [ 48 ]. Under normal circumstances, the level of oxytocin receptor in uterine smooth muscle is low.…”
Section: Discussionmentioning
confidence: 99%
“…It has a strong contractile effect on the uterus at all stages of pregnancy. CTI can induce rhythmic uterine contraction by binding to oxytocin receptors on uterine smooth muscle [ 48 ]. Under normal circumstances, the level of oxytocin receptor in uterine smooth muscle is low.…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 16 In an ex vivo study, one coding and one noncoding OXTR variant altered the oxytocin-induced contractions of uterine tissue strips isolated from pregnant individuals. 17 Although exome sequencing studies have shown that missense variants in the OXTR gene are prevalent in the global human population, 18 the functional effects of most of these variants have not been determined. However, prevalent missense variants in other GPCRs genes lead to aberrant drug responses.…”
mentioning
confidence: 99%
“…Also, homo- or hetero-multimerization of the native receptors may change their pharmacology. Third, there are a number of polymorphic OT receptor variants reported 26 , 27 , 28 that may show differential ligand sensitivity. Testing those variants and a comparison of our results with the OT and V 1A receptor pharmacology of freshly isolated myometrial cells could help clarify if our results are specific for the hTERT-C3 cell line or a general difference between native and recombinant OT receptor pharmacology.…”
Section: Resultsmentioning
confidence: 99%